Pemberian Pupuk Organik Dan Anorganik Untuk Meningkatkan Pertumbuhan Dan Hasil Tanaman Padi (Oryza Sativa L.) Dengan Sistem Of Rice Intensification (SRI): Pemberian Pupuk Organik Dan Anorganik Untuk Meningkatkan Pertumbuhan Dan Hasil Tanaman Padi (Oryza Sativa L.) Dengan Sistem Of Rice Intensification (SRI) - Ni Wayan Nopita Sunarianti; Made Sri Yuliartini; Anak Agung Sagung Putri Risa Andriani (Fakultas Pertanian, Universitas Warmadewa, 2021)
This study aims to determine the interaction of organic fertilizer TOP G2 and Urea, TSP, and KCl on the growth and yield of rice plants using the System Of Rice Intensification. The research was carried out on rice fields in Bresela Village, Payangan District, Gianyar Regency, Bali. From February 17th - June 15th 2020.Using a randomized design a factorial group consisting of 2 factors, namely the concentration of TOP G2 fertilizer consisting of B0: without fertilizer, B1: 2.5 cc/l, B2: 5 cc/l, B3: 7.5 cc/l and the dose of Urea fertilizer. , TSP, and KCl A1: Urea + TSP + KCl (33.75 gr + 11.25 gr + 11.25 gr), A2: Urea + TSP + KCl (67.5 g + 22.5 g + 22.5 g), A3: Urea + TSP + KCl (101.25 g + 33.75 g + 33.75 g). The interaction of TOP G2 organic fertilizers with Urea, TSP and KCl had a significant effect on the maximum number of leaves. TOP G2 organic fertilizer treatment B1, namely 41.01 gr, which was not significantly different from other treatments compared to treatment B3, namely 32.80 gr. The dry weight of grain harvest per hill was higher in treatment A2, namely 40.24 gr, which was not significantly different from treatment A1, namely 32.80 gr.